(untitled) (International Journal of Engineering and Computer Science, 2013)
In Wireless Sensor Network (WSN), Sensor nodes have limited processing capabilities, therefore simplified protocol architecture should be designed to make communications simple and efficient. Due to this limited power supply, every solution elaborated for these networks should be aimed at minimizing the energy consumption. In previous approach, the original data packets are split into a number of sub-packets equal to the number of disjoint paths from source to destination. This approach is applied sequentially in that network which takes more computational time. The proposed approach splits the original messages into several packets such that each node in the network will forward only small sub-packets. The splitting procedure is achieved by applying the Chinese Remainder Theorem (CRT) algorithm. This approach is applied in entire network which takes low computational time. The objective is to improve the energy in wireless sensor network.